Vestibular and oculomotor function in male combat sport athletes. Issue 6 (June 2022) - Brown, Daniel A.; Leung, Felix T.; Evans, Kerrie; Grant, Gary; Hides, Julie A.
Abstract: Objectives: To investigate for differences in vestibulo-ocular function between active male combat sport athletes and a healthy control group. In addition, to explore the relationship between symptom-based outcome measures with vestibulo-ocular function. Design: Cross-sectional. Methods: 40 male adult combat sport athletes and 40 active male control participants were recruited from 4 martial arts schools and a University campus in Queensland, Australia. All participants completed a standardised protocol which was used to assess vestibulo-ocular function. The protocol included 3 components: 1) oculomotor function, 2) benign paroxysmal positional vertigo screening, and 3) vestibulo-ocular reflex function. The Post-Concussion Symptom Scale, Vestibular/Ocular Motor Screening tool and Dizziness Handicap Inventory were used as symptom-based outcome measures. Results: More combat sport athletes had oculomotor abnormalities than control group participants. There were no between group differences in benign paroxysmal positional vertigo, vestibulo-ocular reflex function and the video-head impulse test gain (ms). Combat sport athletes had higher symptom-based outcome scores. The Vestibular/Ocular Motor Screening tool and Dizziness Handicap Inventory were found to have moderate positive relationships with the total number of abnormalities detected in the combat sport group. Conclusions: Vestibulo-ocular function is imperative for combat sport athletes to perform evasive manoeuvres and land their own strikes. The present study findings may aid clinicians in the identification of combat sport athletes with underlying vestibulo-ocular dysfunction, prompting further investigation.